COGNITIVE SCIENCE DAN COGNITIVE DEVELOPMENT DALAM PEMROSESAN INFORMASI (INFORMATION PROCESSING) PADAANAK - Prima, Ellen (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2016)
Cognitive science is a science which studies how human mental processes to influence oneâ€™s behavior. Principal major issue that needs to be known in the understanding of cognitive science and their development is related to how the initial state of cognitive science itself, the mind is adapted, the development process starting from the concrete to the abstract, the conceptual nature of the change, the difference between learning and development, format representation of the underlying changes in development, the role of implicit and explicit cognitions in the development, the role of the association and the rules in the development, the universal development, cognitive domain and how to influence the development of brain structure. There are three difference in the cognitive domain of the most common sense that domain as a module, as the domain of expertise, and domain as a model of mind.Â Ilmu kognitif adalah suatu pengetahuan yang mempelajari tentang bagaimana proses mental manusia dalam mempengaruhi perilaku seseorang. Pokok pembahasan utama yang perlu diketahui dalam memahami ilmu kognitif dan perkembangannya yaitu terkait dengan bagaimana keadaan awal dari ilmu kognitif itu sendiri, pikiran yang teradaptasi, proses perkembangan mulai dari hal yang kongkrit sampai dengan abstrak, sifat konseptual dalam perubahan, perbedaan antara belajar dan pengembangan, format representasi yang mendasari perubahan dalam perkembangan, peran kognisi implisit dan eksplisit dalam perkembangan, peran asosiasi dan aturan dalam perkembangan, perkembangan secara universal, domain kognitif dan bagaimana struktur otak mempengaruhi perkembangan. Ada tiga perbedaan domain kognitif dari indera yang paling umum yaitu domain sebagai modul, domain sebagai bidang keahlian, dan domain sebagai model pikiran.